India - Vietnam Relations: Retrospect & Prospect - Tran Tien, Nguyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
India - Vietnam Relations: Retrospect & Prospect (Edited by Rajaram Panda. Northern Book Centre, New Delhi, Indian. 2016. ISBN: 81-7211-371-4) The book “India-Vietnam relations: Retrospect & Prospect” is the outcome of the International Conference on “India-Vietnam relations: Retrospect & Prospect” organized by ICCR in February 2016 aimed to undertake comprehensive analysis of India-Vietnam relations. The conference was organized at such an important juncture of geo-political terms, when the changing situation is shaping regional politics and East Asia is emerging as powerful states in global affairs. In this context, South and Southeast Asia are facing a difficult period in the area of regional co-operation because of many conflicts. Therefore, each country should unite the people of the region through a culture of peace, stability, friendship and development. Then it may solve the problems up to a certain extent through peaceful means. In that sense, India and Vietnam may play an important and effective role. Overwhelmed with such an effort of bringing intellectuals and scholars from both countries on a common stage to share their views, it will be an excellent opportunity to review the relations of India and Vietnam and take it to higher levels in the years to come. The sections in the volume contain perspectives of scholars, diplomats, activists, opinion makers and cultural historians on the traditional relationships between India and Vietnam. Though the primary focus is on the cultural component of the ties, other dimensions such as economic and security issues are also covered. Specifying few of the unique features that both countries share like cultural affinity and mutual sympathy for those who suffered from colonialism, the two countries maintained mutual trust and new economic opportunities have enhanced cooperation to a great extent. It is not exaggerated to say this is a rare and unique relationship that researchers from both countries should explain. Most of the book’s chapters have pointed out enormous historical evidences that substantiate these views, which can be witnessed more in Central and less in Northern and Southern Vietnam. They agree that this relation can be traced back to the first century or even earlier. China, Indian Buddhism, and Brahmanical culture had great influence and impact on Vietnam. This relation always maintained mutual understanding, respect and co-operation. India is the second largest country in the world with regard to population, the world’s largest democracy and by far the largest country in South Asia, and one of the most diverse and pluralistic nations in the world in terms of official languages, cultures, religions and social identities. The introductory and overview chapter primarily focus on these cultural identities that can be found in the India-Vietnam relations, though very few dimensions such as economic and security issues in this book have taken a center stage in recent times. Besides, the chapters in this volume also contain various sub-themes - viz. historical and cultural linkages; synergy between culture and history; culture fostering India-Vietnam relations; Ho Chi Minh in India & Rabindranath Tagore in Vietnam; Impact of Buddhism & Hinduism over Vietnam’s culture and society and future vision of relations: mutual exchange of ideas. Chapter II focuses on synergy between culture and history with 5 sections. The major discussion of this chapter is to emphasize over the future vision of the bilateral relations between the two countries; economic expansion in the maritime route; cultural diplomacy as a key to foster friendship and explained why the relations were important not only strategically but culturally, also for a better understanding of each other. H. E. Mr. Ton Sinh Thanh Ambassador of S.R. Vietnam in India appreciated the richness of Indian culture and talked about the cultural diplomacy. He said that if the Govt. of India accepts the proposal to erect the statue of President Ho Chi Minh in the capital of India, it will be an excellent symbol of friendship. Chapter III and IV focus on the culture fostering India-Vietnam relations. These two chapters deal with the culture that binds Indian-Vietnamese relations and explore the cultural extensions beyond borders: Indian parallels at Champa as well as sacred treasures in Champa temples – referring to the Indian ancient texts; the cultural bonding between India and Vietnam and the role of Hinduism and Buddhism and aspects of India in Vietnam: Sanskrit/art of Champa/My Son Monument Chapter V, “Ho Chi Minh In India & Rabindranath Tagore in Vietnam” is worthy reading which follows by three different sessions. For Indians, Ho Chi Minh is the great communist revolutionary leader was a great friend of Indian people and it will be an excellent symbol of the Indo-Vietnam friendship. India always stood with Vietnamese people in their struggle against foreign rule and welcomed Ho Chi Minh as a friend of India and is remembered with gratitude in Vietnam. The essays offer valuable insights from both Indian and Vietnamese perspectives. This chapter also deals with section on Tagore from eco-critical perspectives by examining how Tagore’s thoughts on environment were received in Vietnam and why it was of great concern in some period but was ignored in some other period. In modern times, Rabindranath Tagore’s sane counsel for a peaceful Asia found greater acceptance and appeal in Vietnam. The people of Vietnam appreciated Tagore’s advocacy of non-violence, non-confrontational and egalitarian society that encouraged social mobility and this is remembered even today. The flow of Indian religious values and institutions into Vietnam is one of the most remarkable aspects of the Indian-Vietnamese traditional relations. To understand this flow, it is better to read Chapter VI on “Impact of Buddhism & Hinduism over Vietnam’s Culture and Society”. In this chapter, scholars have demonstrated how India’s cultural links were very different from other cultural influences in Vietnam that had an aggressive intent. Indian voyagers who settled in some parts of Vietnam were smoothly integrated into the Vietnamese society. Moreover, we can understand the relations between India and Vietnam by looking at the role of Buddhism and Hinduism and practicing Buddhism in two villages of Red River Delta in Vietnam. The last chapter aimed to visualize the future vision of Indian-Vietnamese relations by mutual exchange of ideas. In this chapter, three sections have mentioned about how to connect the past to the present to unearth synergy; “India-Vietnam: Strategically close, culturally distant” and “India-Vietnam: some leaves from the Parliamentary debates”. Thus, the idea behind this book was to provide a platform for dialogue and an interface between the policy makers, researchers and academics for looking into the future and emerging dynamics of Indian-Vietnamese relations. Given the context of cultural, historical linkages, geo-strategic paradigms and the forces shaping the Retrospect & Prospect of India-Vietnam relations, this sought to deliberate upon the internal political dynamics of Vietnam and the factors determining its foreign policy orientations vis-à-vis the ‘Great Powers’ in the region and its engagement with India at large. About editor: this book is edited by Professor (Dr.) Rajaram Panda, who is currently the Chair of the Indian Council for Cultural Relations (ICCR) India and visiting professor at Reitaku University in Japan. He has presented a number of scholarly papers at national and international seminars and conferences in India, Vietnam, on Indian-Vietnamese’s cultural, economic, political and strategic issues. He is a frequent contributor to leading Indian dailies on current issues of Indian-Vietnamese relations.